FACTORS ASSOCIATED WITH D-DIMER ELEVATION IN PATIENTS WITH VENOUS THROMBOEMBOLIC EVENTS - N. M. Vorobyeva; E. P. Panchenko; A. B. Dobrovolskyi; E. V. Titaeva; O. V. Ermolina; T. V. Balakhonova; Z. B. Khasanova; A. Yu. Postnov; A. I. Kirienko (Российский кардиологический журнал)
Aim. To study the factors associated with elevated D-dimer levels in patients with acute venous thromboembolic events (VTEE). material and methods. The study included 111 patients (76 men and 35 women aged 18–76 years) with a first or repeat episode of deep vein thrombosis (DVT) and/or pulmonary embolism (PE) in the last 2 months. The majority of the patients (n=80) received unfractionated heparin (UFH) for at least 5 days, followed by warfarin (international normalized ratio (INR) control at least once a month; target INR 2,0–3,0). Some patients (n=31) received therapeutic doses of enoxaparin (1 mg/kg subcutaneously, every 12 hours) for at least 30 days, followed by warfarin treatment. D-dimer levels (norm <0,5 mkg/ml) were measured by the latex agglutination method, with the use of “STA LIATEST >® D-DI” reagents (Diagnostica Stago). Results. D-dimer levels varied from 0,02 to 9,96 mkg/ml (median 1,05 mkg/ml, interquartile range 0,49–1,99 mkg/ml) and exceeded the upper norm limit in 74% of the patients. There was a positive association between D-dimer levels and thrombus “size” (r=0,304; p<0,001), and a negative association between D-dimer levels and >< 0,001), and a negative association between D-dimer levels and thrombus “age” (r=-0,418; p<0,001). Predictors of D-dimer elevation were identified among 150 demographic, anthropometric, anamnestic, clinical, laboratory, genetic, or ultrasound parameters and VTEE risk factors. The results of the multivariate stepwise regression analysis demonstrated that female gender, chronic heart failure (CHF), VTEE symptom duration ><28 days, and thrombus “size” >< 0,001). Predictors of D-dimer elevation were identified among 150 demographic, anthropometric, anamnestic, clinical, laboratory, genetic, or ultrasound parameters and VTEE risk factors. The results of the multivariate stepwise regression analysis demonstrated that female gender, chronic heart failure (CHF), VTEE symptom duration <28 days, and thrombus “size” >< 28 days, and thrombus “size” < 6 points were independent predictors of D-dimer elevation in the acute period of DVT/PE. Conclusion. D-dimer levels, measured 32 (23–44) days after the development of DVT/PE symptoms, were elevated in 74% of the patients. D-dimer elevation in the acute period of VTEE was associated with female gender, CHF, “age” and “size” of the thrombus.